Inclusion of fluorophores in cyclodextrins: a closer look at the fluorometric determination of association constants by linear and nonlinear fitting procedures. (14th December 2017) - Hutterer, Rudi
Abstract: The author discusses methods for the fluorometric determination of affinity constants by linear and nonlinear fitting methods. This is outlined in particular for the interaction between cyclodextrins and several anesthetic drugs including benzocaine. Special emphasis is given to the limitations of certain fits, and the impact of such studies on enzyme-substrate interactions are demonstrated. Both the experimental part and methods of analysis are well suited for students in an advanced lab.